Phase-change-compensation low-thermal-expansion-coefficient resin formula and preparation and use method of composite prepreg tape of phase-change-compensation low-thermal-expansion-coefficient resin
By adding capsules to the resin-based composite material to coat nanotin micropowder, the thermal stress problem caused by mismatch of linear expansion coefficients in ultra-low temperature environments is solved, and the effect of low expansion coefficient and zero internal stress is achieved. It is suitable for space, deep sea and new energy hydrogen storage fields.
Patent Information
- Application Number
- CN202510035601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The thermal stress mismatch of existing resin-based composite materials in ultra-low temperature environments due to mismatch of linear expansion coefficients, resulting in interface debonding and nucleation and expansion of low-temperature tensile microcracks, affecting their application in space, deep sea and new energy hydrogen storage fields.
The resin formula is adopted to compensate for low thermal expansion coefficient of phase change, and by adding capsules to the resin formula to coat nanotin micropowder, absorbing the curing and exothermic heat of the resin-based composite material, suppressing temperature rise and curing shrinkage stress, and volume expansion is generated at low temperature through the phase change of the tin micropowder, compensating for volume shrinkage of the resin.
It achieves a low expansion coefficient comparable to that of the composite resin matrix and zero internal stress at the design temperature, extends the service life of the material and reduces hydrogen leakage, and is suitable for hydrogen storage and oxygen storage in low and ultra-low temperature environments.
Smart Images

Figure CN119823589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of resin-based composite materials and preparation technology, and in particular to a phase change compensation low thermal expansion coefficient resin formula and a composite prepreg tape preparation and use method thereof. Background Art
[0002] In recent years, my country has invested a lot of manpower and material resources in scientific and technological research in the fields of space, deep sea and hydrogen energy, and has achieved remarkable results, greatly enhancing its scientific and technological strength and comprehensive national strength in related fields.
[0003] First of all, low thermal expansion coefficient resin-based composite materials are the inevitable choice for conducting low-cost space activities.
[0004] The rockets used for space exploration are made of cryogenic propellants represented by liquid hydrogen and liquid oxygen, which have the characteristics of high specific impulse, simple chemical reaction process, non-toxicity and pollution-free. Future space activities such as manned space flight, lunar landing and deep space exploration have listed liquid hydrogen and liquid oxygen cryogenic fuels as the preferred propellants. Replacing metal with lightweight and high-strength carbon fiber reinforced composite materials (CFRP) can reduce the weight of the tank by 30% and the cost of the aircraft by 37%.
[0005] There are two types of cryogenic fuel tanks for launch vehicles: one is a disposable launch vehicle and the other is a reusable rocket. The latter greatly reduces the cost of space launches. Launcher reuse technology is considered to be one of the inevitable ways for humans to leave the earth and even migrate to Mars. For disposable rockets, the main consideration is the strength of the tank material and the ability to withstand ultra-low temperature strain. The main research is to break through the strength of CFRP in ultra-low temperature environments, the toughness of epoxy matrix and the thermal stress bottleneck; for reusable rockets, the fuel tank undergoes multiple cryogenic propellant filling processes. In addition to considering the strength and toughness of the tank material in ultra-low temperature environments, it is also necessary to consider the reusability of the tank after temperature changes. The extreme thermal stress caused by the mismatch of linear expansion coefficients between carbon fiber and resin after ultra-low temperature / room temperature thermal cycle treatment leads to debonding of the matrix resin interface and the nucleation and expansion of low-temperature tensile microcracks on fatigue life and gas diffusion. CFRP is generally composed of 40% to 60% volume fraction of carbon fiber and resin matrix. The carbon fiber determines the main strength of CFRP, and the resin matrix affects the stress transfer, strain and fatigue strength of CFRP. In ultra-low temperature environments, the resin molecular segments freeze and shrink, resulting in reduced toughness. The linear expansion coefficient of the resin is quite different from that of the carbon fiber. For example, at room temperature, the linear expansion coefficient of the TDE-85 model resin is 44.4×10-6 / ℃, and the axial linear expansion coefficient of the carbon fiber is 0.7×10-6 / ℃, which is dozens of times different. In ultra-low temperature environments, thermal stress mismatch occurs at the interface between carbon fiber and resin. After thermoforming at room temperature, liquid hydrogen at -253℃ or liquid oxygen at -183℃ is added. Such a high temperature difference and thermal expansion coefficient difference will cause very large thermal stress between the fiber and the resin, resulting in interface debonding, and the matrix loses the ability to transfer external loads to adjacent fibers, causing microcracks at the interface between the carbon fiber and the resin matrix. Therefore, developing low thermal expansion coefficient materials and designing low-temperature zero-shrinkage composite ultra-low temperature storage tanks are the inevitable way to reduce the cost of my country's space exploration and accelerate the pace of space exploration.
[0006] Secondly, low thermal expansion coefficient composite materials are the inevitable choice for deep-sea exploration activities.
[0007] Deep-sea research is necessary for the development of science and technology. From a scientific point of view, exploring the deep sea can help humans gain a deeper understanding of the mysteries of the ocean and the earth. Whether it is the circulation of greenhouse gases or the source of long-term climate change, they can be traced back to the deep sea. In addition, the seabed is the closest place to the interior of the earth. Deep-sea research is conducive to revealing the laws of plate movement and peeking into the scientific truth of the interior of the earth.
[0008] Deep-sea research is necessary for economic development. The deep sea is rich in minerals, oil and gas, and biological resources. At present, offshore oil production accounts for 30% of the world's production, ranking first in the marine economy, and the fastest growing is deep-water oil fields. In recent years, 70% of the world's major oil and gas discoveries have come from waters more than 1,000 meters deep. There are abundant resources to be developed on the seabed, and it is still in the initial stage. Many technologies related to the development of deep-sea resources need to be developed and verified. my country's deep-sea technology started late but has developed rapidly and achieved remarkable results.
[0009] Deep diving is one of the three major means of exploring the mysteries of the deep sea today. It is an important exploration method that can directly explore the deep sea and quickly take samples from the deep sea. However, the seawater increases by one atmosphere of pressure every 10 meters, and deep-sea diving can only be carried out in a certain pressure-resistant container. In recent years, with the support of communication and artificial intelligence technologies, unmanned submersibles have become the first choice for many scientific exploration projects. In the future, they will also become a hot area for the development of unmanned underwater weapons in various countries, and become a reliable and important part of the sea denial strategy. Traditional submersibles are mostly made of titanium alloys with large thickness, high compression strength and high corrosion resistance. They have high reliability but high material and processing costs, which greatly limits the development and utilization efficiency of unmanned submersibles. Carbon fiber reinforced resin-based composite materials are the most ideal materials for making unmanned submersibles because of their high specific strength, specific modulus, corrosion resistance, designability and easy integration. However, the compressive strength of carbon fiber reinforced resin-based composite materials is much lower than their tensile strength of more than 2000 MPa. In addition, the shell thickness of deep-sea shells is more than tens of millimeters. During the integrated curing and molding process, the heat of material reaction cannot be dissipated from the thick plate in time, resulting in temperature rise, which further accelerates the reaction exotherm. The temperature rise in a vicious cycle affects the performance of structural materials. Finally, the resin material has a high curing shrinkage rate and thermal expansion coefficient, which makes the cured resin material prone to crack nucleation and expansion due to internal stress. Under the high pressure of tens or hundreds of MPa in the deep sea, seawater diffuses along the cracks into the material, accelerating the failure of materials and equipment, causing unnecessary losses to deep-sea research.
[0010] Secondly, low thermal expansion coefficient composite materials are the inevitable choice for product iteration and upgrading in the field of new energy hydrogen storage.
[0011] At the same time, in the field of new energy hydrogen energy utilization for civilian use, the design and production process of liquid hydrogen or high-pressure hydrogen cylinders may require low thermal expansion coefficient composite materials for low-temperature storage tanks. In addition to designing and producing storage tanks with higher pressure, larger volume, and more filling cycles, composite materials produced by good low thermal expansion coefficient resins can also reduce interface and matrix cracks, thereby reducing hydrogen leakage. It is an inevitable way to upgrade the technology of the new generation of hydrogen storage cylinders.
[0012] In addition, the dry prepreg tape used for high-pressure shell winding has the advantages of long material storage period, uniform fiber distribution, uniform winding tape width, and less prone to fiber micro-buckling during the winding process, which is very suitable for the production of pressure-resistant composite products.
[0013] Aiming at the above-mentioned major scientific and technological and livelihood needs in aerospace, deep-sea equipment, new energy gas cylinders, etc., the present invention provides a high-performance phase-change heat-absorbing, low thermal expansion coefficient resin formula system and a prepreg tape preparation method thereof, which perfectly solves the special needs of these fields for composite materials without almost increasing the cost of existing materials. Summary of the invention
[0014] The purpose of the present invention is to solve the problems in the existing background technology. In order to achieve the above invention purpose, the present invention provides the following technical solution: a phase change compensation low thermal expansion coefficient resin formula, the formula composition is: 30-60 parts of liquid resin, 10-30 parts of solid resin, 5-15 parts of toughening agent, 6-50 parts of curing agent, 1-10 parts of accelerator, 10-80 parts of coated nano-tin alloy, and 0.1-5 parts of auxiliary agent.
[0015] As a preferred technical solution of the present invention, the liquid resin is one or two of difunctional, trifunctional, and tetrafunctional thermosetting resins.
[0016] As a preferred technical solution of the present invention, the solid resin is solid bisphenol A type or solid phenolic modified bisphenol A type resin.
[0017] As a preferred technical solution of the present invention, the toughening agent is one or two of phenoxy resin, cyanate ester, PKHH, PEK, PEEK, PEKK, PI, carboxyl-terminated nitrile rubber, nano core-shell toughening agent, modified graphene, and carbon nanotubes.
[0018] As a preferred technical solution of the present invention, the curing agent is one or both of dicyandiamide and imidazole epoxy curing agent.
[0019] As a preferred technical solution of the present invention, the accelerator is one or both of urea or imidazole curing agents.
[0020] As a preferred technical solution of the present invention, the coated nano-tin alloy is carboxyl-terminated nitrile rubber, hydroxyl-terminated nitrile rubber, polyurea, polyurethane, polyimide coated nano-tin or tin alloy, with a particle size of 0.05-10 microns, a tin content of more than 80% in the alloy, and a coated capsule layer thickness of 50nm-2um.
[0021] As a preferred technical solution of the present invention, the auxiliary agent includes one or two of an internal mold release agent, paraffin, a coupling agent, a wetting agent, and a defoaming agent.
[0022] As a preferred technical solution of the present invention, the resin system is prepared as follows:
[0023] Step S1: The tin powder is slightly oxidized on the surface in the air, treated with a coupling agent, and a sol-gel method is used to prepare capsule-coated tin powder. A certain amount of liquid resin is taken, and the capsule-coated tin powder is added to the liquid resin by stirring and three-roll grinding to make it evenly dispersed to form a tin powder pre-dispersed paste for use.
[0024] Step S2: Take a certain amount of liquid resin, add the toughening agent into the liquid resin, heat it up, and stir it at high speed to make it dissolve evenly in the resin to form a toughening masterbatch for use.
[0025] Step S3: Take a certain amount of liquid resin, add curing agent into the liquid resin, stir, and grind it evenly by three-roll grinding to form a curing agent pre-dispersed paste for use.
[0026] Step S4: Take a certain amount of liquid resin, add the accelerator into the liquid resin, stir, and grind it evenly by three-roll grinding to form an accelerator pre-dispersed paste for use.
[0027] Step S5: Add toughening masterbatch, liquid resin and solid resin to the dispersion axe in proportion, heat and stir, and vacuum to remove bubbles while stirring. After the materials are evenly mixed, cool to 70-80°C, add additives, curing agent pre-dispersed paste, tin powder dispersion paste and accelerator pre-dispersed paste in sequence, stir and mix evenly, discharge the materials, bag them and cool them to room temperature in a ventilated place for use.
[0028] As a preferred technical solution of the present invention, the preparation of the dry prepreg tape system is as follows:
[0029] Step S1: Design a carbon fiber prepreg tape mold for hot soaking cooling drawing method. The mold is equipped with a resin supply system with vacuum degassing and heating functions, a heating module, a refrigeration and heating temperature control module, a cooling end and a vacuum degassing module. The mold openings at both ends have rounded corners, the cavity has a slight taper from the inlet to the outlet, and the inner wall is chrome-plated and mirror-polished.
[0030] Step S2: The carbon fiber is led out from the tension release frame, and after being spread by the yarn spreading device, it enters the mold under the action of the rear traction and winding device and continuously moves forward at a set speed. The resin enters the mold cavity under the action of the glue injection machine and the fiber traction and drag. The resin continues to heat up and melt inside the mold to fully infiltrate the fiber, and then gradually cools down and evacuates during the cooling process. The resin itself with a certain viscosity acts as a gas sealant at both ends of the mold cavity. Under the combined action of temperature, mold extrusion and vacuum, the degassing and compaction process of the resin material is completed.
[0031] Step S3: Under the action of the traction tension of the die mouth, the material continues to move forward into the low-temperature solidification stage. As the temperature decreases, the viscosity of the resin attached to the fibers increases sharply and gradually has a certain load-bearing capacity to bond the fibers into a whole. In this process, the temperature decrease causes the material to cool and shrink and fall off from the inner wall of the mold. The release agent originally dissolved in the resin system is reduced in solubility due to the temperature decrease and precipitates to the surface of the material to lubricate and reduce the resistance of the solid material further out of the mold cavity. The low-temperature solid resin attached to the fiber surface is pulled out of the mold cavity with the fiber under the fiber traction and enters the low-temperature closed traction chamber.
[0032] Step S4: The low-temperature prepreg tape enters a low-temperature closed traction chamber. The low temperature ensures that the resin is hard and can bear the load. At the same time, the closed chamber can prevent external moisture from entering and producing condensed water. The traction device in the traction chamber gives the low-temperature prepreg tape a continuous forward traction force, driving the fiber into the mold, cooling the prepreg tape material and removing it from the mold cavity, thereby realizing the continuous production of the prepreg tape.
[0033] Step S5: After the prepreg tape comes out of the low-temperature traction chamber, it is softened by hot air heating, coated with a hot roller and rolled up to form a prepreg tape material for dry winding.
[0034] Step S6: The rolled prepreg tape material after coating and rolling is sealed, dried, and stored away from light at room temperature of 25° C. to 30° C. for later use.
[0035] As a preferred technical solution of the present invention, the dry prepreg tape material is used to prepare a controllable shell:
[0036] Step S1: using molding sand and low melting point metal to process and prepare a winding core mold according to the design size of the shell, and covering the vacuum air bag and air guide felt vacuum forming material.
[0037] Step S2: Wrap the prepared prepreg tape within its validity period layer by layer on a core mold with a vacuum system under a certain tension using a winding device according to the design parameters, remove the wrapped preform and place it into a designed circular mold shell coated with a release agent, apply sealant to the mold gap and lock it with screws.
[0038] Step S3: Wrap the outer layer of the mold and the inner wall of the shell with a composite material-molded strip vacuum film, seal with a sealing strip, and put the whole into an autoclave after connecting to a vacuum device.
[0039] Step S4: After continuous vacuuming, the autoclave is slowly heated according to the set program in the vacuuming state, and the vacuuming is continued and the shell is solidified according to the set process. As the temperature in the autoclave gradually increases, the composite shell resin gradually softens and flows, and fills the small amount of gaps generated in the process under the action of vacuum, and the small amount of bubbles entrained in the resin gradually grows and breaks and discharges under the action of vacuum. At this time, compressed air is introduced into the autoclave. Because the mold shell and the inner wall of the product are simultaneously subjected to the sum of the air pressure of the external compressed air and the vacuum degree, which is called the total air pressure, the total air pressure on the outer wall acts on the circular mold shell, and the total air pressure on the inner wall acts on the winding shell, so that the bubbles in the shell resin are further squeezed and crushed and discharged, and at the same time, the entire shell is subjected to the total air pressure of the radial outward expansion, so that the shell is close to the inner wall of the molding mold to obtain a circular product shape, and at the same time, the shell expands outward while the axially wound fiber tension is minimized to minimize the microscopic buckling phenomenon of the internal fiber of the product during the process, ensuring the performance of the material compression performance and preventing the accidental failure of the product caused by the uncontrollable buckling of the local fiber of the shell, providing a safe and reliable pressure-bearing shell for deep-sea activities. At the same time, during the molding process of thick-walled composite materials, when the middle part of the material releases heat, the filler tin powder will absorb heat and reduce the temperature rise. When the temperature rises to the tin phase change temperature of 161°C, the tin powder undergoes a phase change and produces a volume expansion of 11%, which compensates for the molding stress caused by excessive heat release and curing shrinkage of the resin. When the thick shell product is cured and exothermic, the temperature rises to 231°C, and the filler tin powder undergoes a solid-liquid transition and absorbs a large amount of heat, avoiding the thermal decomposition of the material when the temperature of the thick-walled composite material rises to 250°C, which affects the product strength. After the curing is completed, the shell is gradually cooled to room temperature to complete the transformation of γ-Sn to β-Sn and further cooled to below 13°C. At this time, a slow transformation of β-Sn to a-Sn occurs, and the volume expands by 13.7% relative to the volume of γ-Sn when the curing is completed, reducing or eliminating the shrinkage internal stress inside the cured resin material, reducing the germination and expansion of resin cracks caused by the release of internal stress during repeated loading during the service of the material, and avoiding the premature structural damage and failure of the composite product due to the nucleation and expansion of internal stress cracks.
[0040] Step S5: The internal sand core mold is removed by physical and chemical methods to obtain a high-performance shell product.
[0041] Compared with the prior art, the present invention has the following beneficial effects: In the scheme of the present invention:
[0042] 1. By adding capsule-coated nano-tin powder to the resin formula system, the curing heat of the resin-based composite material is absorbed to suppress the temperature rise and produce curing shrinkage stress. When the cured composite product is used at a temperature below 13°C, the metal tin powder phase change produces volume expansion, compensating or offsetting the volume shrinkage of the resin caused by curing and cooling, thereby achieving a low expansion coefficient comparable to that of the fiber in the composite resin matrix and zero internal stress at the design temperature, meeting the special environmental material requirements in the field of low-temperature and ultra-low-temperature hydrogen and oxygen storage. Due to the stability of a-Sn, the material will not undergo phase change when used at a temperature far below the tin melting point of 230°C, which will affect the volume expansion effect of the tin microcapsules.
[0043] 2. Add capsule-coated tin powder to the resin formula system. By controlling the particle size and amount of tin powder added, the effect of no internal stress or even reverse stress can be achieved, thereby inhibiting the nucleation and expansion of cracks inside the material, and achieving the control of leakage safety problems caused by the diffusion of high-pressure seawater or gas molecules in the storage tank along the microcracks.
[0044] 3. The method for preparing prepreg tapes with high-temperature fiber impregnation and low-temperature demoulding effectively avoids the strength loss caused by the inevitable cutting of fibers when preparing prepreg tapes by slitting traditional prepregs; solves the gap and overlap problems of uneven distribution of fibers and resins in traditional wet winding that affect structural performance, avoids the problem of uneven distribution of microscopic local materials and reduced bearing capacity, and improves the bearing capacity and reliability of the shell structure. The method has a clear and reliable technical route and strong continuous production capacity, which can effectively reduce process costs while improving performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 A schematic diagram of the structure of capsule-coated tin microspheres provided by the present invention;
[0046] Figure 2 Tin microspheres and their dispersed fracture micromorphology provided by the present invention;
[0047] Figure 3a A schematic diagram of the structure of a prepreg tape continuous production device according to Example 1 of the present invention;
[0048] Figure 3b A schematic diagram of the structure of a continuous production equipment for prepreg tapes according to Example 2 provided by the present invention;
[0049] Figure 4 The schematic diagram of the carbon fiber reinforced tin powder modified resin system without low temperature internal stress provided by the present invention;
[0050] Figure 5 The present invention provides a graph showing the relationship between the amount of tin powder added and the volume shrinkage of the resin matrix. DETAILED DESCRIPTION
[0051] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0052] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents some embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments of the present invention and the features and technical solutions in the embodiments can be combined with each other without conflict. It should be noted that similar numbers and letters represent similar items in the following drawings. Therefore, once an item is defined in one drawing, it does not need to be further defined and explained in subsequent drawings.
[0053] Specific embodiment 1: A phase change compensation low thermal expansion coefficient resin formula, the formula composition of which is: 70 parts of liquid resin AG80, 15 parts of solid resin 019, 15 parts of PKHH toughening agent, 8 parts of dicyandiamide, 1.5 parts of N-(2-hydroxyphenyl-N',N'-dimethylurea, 40 parts of polyurethane-coated 2um diameter tin powder, 1 part of internal release agent, and 1 part of coupling agent.
[0054] Step S1: 40 parts of tin powder are slightly oxidized in the air, and the tin powder is surface treated with silane coupling agent KH570, and polyurethane microcapsule-coated tin powder is prepared by sol-gel method and in-situ polymerization method. After filtering and washing, 15 parts of AG80 liquid resin are added to stir and disperse, and the mixture is ground three times on a three-roll mill, and the residual solvent is removed by suction to form a uniformly dispersed tin powder paste for use.
[0055] Step S2: Take 30 parts of AG80 resin, add 15 parts of PKHH into the liquid resin while stirring and heating until PKHH is completely dissolved in the resin, and then cool down to form a toughening masterbatch for use.
[0056] Step S3: Take 15 parts of AG80 resin, add 8 parts of dicyandiamide curing agent into the liquid resin, stir, and grind with three rollers to disperse evenly to form a curing agent pre-dispersed paste for later use.
[0057] Step S4: Take 10 parts of AG80 resin, add 1.5 parts of polyurea accelerator into the liquid resin, stir, and grind with three rollers to disperse evenly to form an accelerator dispersion paste for later use.
[0058] Step S5: Add 45 parts of toughening masterbatch and 15 parts of 019 solid resin to the dispersion kettle in proportion, heat and stir at 135°C, vacuum and remove bubbles while stirring, and cool the materials to 70-80°C after mixing evenly. Add auxiliary agent, curing agent pre-dispersed paste, tin powder dispersion paste and accelerator pre-dispersed paste in sequence, stir and disperse evenly, put the materials on the press and put them into a 5kg / bag plastic bag, place them flat on an iron plate rack in a ventilated place to cool to room temperature for use.
[0059] (2) Preparation of dry prepreg tape system, such as Figure 3a As shown:
[0060] Step S1: Design a carbon fiber prepreg strip mold 6 for hot-dip cold demoulding, which has the following features: the mold cavity is a rectangular cross-section with rounded corners, the mold has a taper of 0.1° from the inlet to the outlet for easy demoulding, and the inner wall of the cavity is chrome-plated and mirror-polished. The mold is equipped with a refrigeration sealing ring 7, a heating module 8 controlled by a circulating medium 10, a resin injection system 9 with vacuum degassing and heating functions, an intermediate temperature control module 11 controlled by a circulating medium 12, a cooling module 13 controlled by a cooling medium 15, and a vacuum degassing system 14 structure from the inlet to the outlet.
[0061] Step S2: The carbon fiber 2 is drawn out from the carbon fiber reel 1 with tension control, and the tension closed-loop control is composed of a tension detection shaft 5 and a control circuit; the carbon fiber 2 is spread into a widened fiber with a certain width and thickness and uniform fiber dispersion through hot air blowing 3 and a vibrating yarn spreading device 4;
[0062] Step S3: The widened fiber enters the mold through the cooling sealing plate 7 under the traction of the rear-stage traction device 17 and the winding device 23 and moves steadily forward at the set traction speed; the mold inlet end is provided with a heating sleeve 8 with heat circulation medium heating, and the heating sleeve is provided with a glue injection machine interface 9 connected to the mold cavity and with heating and vacuum degassing functions. The matrix resin which is solid at room temperature enters the hot mold cavity through the glue injection port 9 by the glue injection machine pressure after being heated and degassing at the glue injection machine, and is further heated and melted in the hot mold cavity. The low-viscosity resin in the hot mold cavity fully infiltrates the widened fiber 2 in the mold cavity under the vacuum, glue injection machine pressure and fiber capillary action. The mold cavity is at the mold inlet cold plate 7 and hot plate 8 Under the joint action of the temperature gradient from the injection port 9 to the cold plate at the mold entrance, when the resin flows toward the mold entrance, the viscosity increases and the fluidity decreases due to the decrease in temperature. At the same time, the fiber moving forward in the mold cavity drives the resin to move toward the exit direction. The moving traction force of the resin and the injection pressure form a balance to achieve the effect of resin sealing at the mold entrance; the fiber and resin continue to move forward under the action of traction tension, and the bubbles of the fiber and the resin after passing through the temperature control module 11 and the refrigeration module 13 are released under the vacuum action and gradually cooled to a solid. The release agent in the resin has a lower solubility in the resin due to the cooling and precipitates to the surface of the material to play a lubricating and demolding role. The resin carried by the fiber is cooled and solidified into a cold and hard solid, and is pulled out of the mold cavity as a whole by the traction force generated by the crawler traction machine 17 and the winder 23 in the closed low-temperature drying box 16 to form a solid prepreg material 18 with uniform thickness, width, material distribution and low air void ratio;
[0063] Step S4: the solid prepreg tape material 18 is softened under the heating action of the hot air pipes 19 and 20 to prevent the generation of condensed water on the surface; the polyethylene plastic protective film 21 is hot-pressed and adhered to the surface of the prepreg tape material by the hot roller 22, and is wound into a roll by the prepreg tape winding device 23, and 1 to 2 more circles of polyethylene protective film 21 are wrapped around the outer surface, and fixed with tape to prevent loosening, and the roll is taken out, put into a sealed bag, packed, and stored for later use.
[0064] (3 large thickness, low shrinkage shell can be controlled:
[0065] Step S1: using fiber and resin reinforced molding sand and low melting point metal to process and prepare a winding core mold according to the design size of the shell, and covering the vacuum air bag and air guide felt vacuum forming material.
[0066] Step S2: The prepared prepreg tape within the validity period is wound layer by layer on the core mold under a certain tension using a winding device according to the design parameters, and the wound preform is removed and placed in a designed circular mold shell coated with a release agent, and the mold gap is sealed with sealant and locked with screws.
[0067] Step S3: Lay demoulding cloth, breathable felt, and silicone shell in the shell cavity, and use a composite molding vacuum bag to wrap the outer layer of the mold and the inner wall of the shell as a whole, seal with a sealing strip, connect the vacuum device, and put the whole into the autoclave.
[0068] Step S4: After continuous vacuuming and debubbling, the temperature is slowly raised, and the shell is cured according to the set process. As the temperature in the autoclave gradually increases, the composite shell resin gradually softens and fills the vacuum gap, and the small amount of bubbles entrained in the resin gradually grows and breaks and discharges under the action of vacuum. Compressed air is introduced into the autoclave. Because the mold shell and the inner wall of the product are simultaneously subjected to the combined air pressure of the external compressed air and the vacuum degree, that is, the total air pressure, the total air pressure on the outer wall acts on the circular mold shell and is borne by the annular shell. The internal total air pressure acts on the wound shell, so that the bubbles in the shell resin are further squeezed and crushed and discharged. At the same time, the entire shell is subjected to the total air pressure of the radial outward expansion, so that the shell slightly expands outward and closely adheres to the inner wall of the molding mold to obtain a product of designed size and shape. At the same time, the shell expands outward to tension the radially wound fibers, minimize the micro-buckling of the fibers during the process, and ensure that the material will not lose its bearing capacity due to local fiber buckling failure under high compression stress levels, providing a safe and reliable pressure-bearing shell for deep-sea personnel and equipment. At the same time, during the molding process of thick-walled composite materials, when the middle part of the material releases heat, the filler tin powder will absorb heat, slowing down the temperature rise of the material caused by the reaction heat. When the middle temperature reaches 161°C, the tin powder undergoes a phase transformation and produces an 11% volume expansion, compensating for the internal shrinkage stress of the product caused by the resin curing shrinkage and the crack nucleation and expansion problems it brings. After the curing is completed, the shell is cooled to room temperature to complete the transformation of the metal tin from γ-Sn to β-Sn, and further cooled to below 13°C. At this time, a slow transformation of β-Sn to a-Sn occurs. The volume relative to the curing is completed. The volume of γ-Sn expands by 13.7%, so that the shell material matrix resin is in a state of no internal stress at the service temperature.
[0069] Step S5: taking out the internal sand core mold by physical and chemical methods to obtain a high-performance shell product.
[0070] Specific embodiment 2: A latent, low exothermic, low shrinkage stress pressure-resistant and tough resin system, whose formula consists of: 128-60 parts of liquid resin, 019-15 parts of solid resin, 12 parts of PKHH toughening agent, 6 parts of dicyandiamide, 2 parts of modified imidazole accelerator, 30 parts of terminal carboxyl-modified nitrile rubber coated with 1um diameter tin powder, and 1.5 parts of internal release agent.
[0071] Step S1: 30 parts of tin powders are slightly oxidized on the surface in the air, and silane coupling agent KH570 is used for surface treatment, and it is standby. Rubber-coated tin powder is prepared using sol-gel method, and the specific method is to gradually drip end-carboxyl modified nitrile rubber to solution saturation in alcohol in a manner of heating while stirring, add tin powder surface-treated by coupling agent, and cool while stirring. As the temperature decreases, the modified rubber dissolved in the solution gradually precipitates from the solution and is attached to the surface of the tin powder, forming a rubber capsule wall with a certain thickness. After filtering and cleaning, 10 parts of liquid resin are added to be stirred and dispersed, and ground three times on a three-roll grinder, and the residual solvent is filtered to form a uniformly dispersed tin powder paste for standby.
[0072] Step S2: Take 25 parts of 128 resin, add 12 parts of PKHH into the liquid resin while stirring and heating until PKHH is completely dissolved in the resin, and then cool down to form a toughening masterbatch for use.
[0073] Step S3: Take 15 parts of resin, add 6 parts of dicyandiamide curing agent into the liquid resin, stir, and grind with three rollers to disperse evenly to form a curing agent pre-dispersed paste for later use.
[0074] Step S4: Take 10 parts of 128 resin, add 2 parts of modified imidazole accelerator into the liquid resin, stir, and grind with three rollers to disperse evenly to form an accelerator dispersion paste for later use.
[0075] Step S5: Add 42 parts of toughening masterbatch and 15 parts of 019 solid resin to the dispersion kettle in proportion, heat and stir at 135°C, and vacuum and remove bubbles while stirring. After the materials are mixed evenly, cool to 70-80°C, add curing agent pre-dispersed paste, tin powder dispersion paste and accelerator pre-dispersed paste, 1 part of internal release agent in sequence, stir and disperse evenly, put the materials on the press and put them into a 5kg / bag plastic bag, place them flat on an iron plate rack in a ventilated place to cool to room temperature for use.
[0076] (2) Preparation of dry prepreg system:
[0077] Step S1: Design a carbon fiber prepreg strip mold 6 for hot-dip cold demoulding, which is composed of: a mold cavity with a flat strip cross-section with semicircular ends, a 0.05° taper from the inlet to the outlet for easy demoulding, and a chrome-plated and mirror-polished inner wall of the cavity. From the inlet to the outlet, the mold is equipped with a refrigeration sealing ring 7, a sealed cavity shell 8 with a vacuum interface 9, a cooling sealing ring 7 and a closed overflow resin recovery barrel 10 connected thereto, a heating module 11 with a vacuum interface 9, a heat preservation module 12, and a cooling module 13 controlled by a cooling medium 15.
[0078] Step S2: the carbon fiber 2 is drawn out from the carbon fiber reel 1 with tension control, and the tension closed-loop control is composed of a tension detection shaft 5 and a control circuit; the carbon fiber 2 is blown by hot air 3 and spread by an ultrasonic vibration spreading device 4 into a widened fiber with a certain width, thickness and uniform fiber dispersion;
[0079] Step S3: The widened fiber enters the bottom of the glue pool 6 with heating function through the cooling sealing plate 7 under the traction of the rear traction section 17 and the winding device 21, and enters the vacuum heating shell 8 sealed by the cold plate 7 after exiting the glue pool. The resin continues to move forward after completing the initial infiltration and defoaming of the fiber in the vacuum heating chamber, and the excess resin flows into the resin collection container 10 after passing through the slit of the cold plate 7; under the action of traction force, the fiber and resin continue to move forward and pass through the mold cavity heated by the heating sleeve 11, the mold cavity controlled by the micro-heat heating module and the refrigeration module in turn. While the fiber-attached resin gradually hardens with the temperature gradient of the cooling, bubbles are continuously released under the action of vacuum, and the release agent in the resin is precipitated to the surface of the material due to the reduced solubility in the resin due to the cooling. The traction force generated by the crawler traction machine 15 and the winder 21 in the closed low-temperature drying box 14 continuously pulls the prepreg material lubricated by the release agent precipitated on the surface of the material out of the mold, forming a solid prepreg material 16 with uniform thickness, width, material distribution and low air void ratio;
[0080] Step S4: the solid prepreg tape material 16 is softened and the surface condensed water is removed under the heating action of the hot air pipes 17 and 18; the polyethylene plastic protective film 19 is adhered to the surface of the prepreg tape material by the hot roller 20, and is wound into a roll by the prepreg tape winding device 21, and the polyethylene protective film 20 is wrapped around the outer surface for 1 to 2 more times and fixed with tape to prevent loosening, and the roll is removed, put into a sealed bag, packed and stored for later use.
[0081] (3 large thickness, low shrinkage shell can be controlled:
[0082] Step S1: Prepare the winding core mold according to the designed size. The core mold consists of a central core shaft, an inner membrane with a large diameter edge and a removable baffle, and a surface insert. It is assembled before use and clamped with baffles at both ends. After use, it is removed from the equipment, the baffles at both ends are removed, the core mold and the inner membrane are pulled out, and the insert is removed inward along the radial direction using tools.
[0083] Step S2: The prepared prepreg tape within the validity period is wound layer by layer on the core mold under a certain tension using a winding device according to the design parameters, and the wound preform is removed and placed in a designed circular mold shell coated with a release agent, and the mold gap is sealed with sealant and locked with screws.
[0084] Step S3: Lay demoulding cloth, breathable felt, and silicone shell in the shell cavity, and use a composite molding vacuum bag to wrap the outer layer of the mold and the inner wall of the shell as a whole, seal with a sealing strip, connect the vacuum device, and put the whole into the autoclave.
[0085] Step S4: After continuous vacuuming and debubbling, the temperature is slowly raised, and the shell is cured according to the set process. As the temperature in the autoclave gradually increases, the composite shell resin gradually softens and fills the vacuum gap, and the small amount of bubbles entrained in the resin gradually grows and breaks and discharges under the action of vacuum. Compressed air is introduced into the autoclave. Because the mold shell and the inner wall of the product are simultaneously subjected to the combined air pressure of the external compressed air and the vacuum degree, that is, the total air pressure, the total air pressure on the outer wall acts on the circular mold shell and is borne by the annular shell. The internal total air pressure acts on the wound shell, so that the bubbles in the shell resin are further squeezed and crushed and discharged. At the same time, the entire shell is subjected to the total air pressure of the radial outward expansion, so that the shell slightly expands outward and closely adheres to the inner wall of the molding mold to obtain a product of designed size and shape. At the same time, the shell expands outward to tension the radially wound fibers, minimize the micro-buckling of the fibers during the process, and ensure that the material will not lose its bearing capacity due to local fiber buckling failure under high compression stress levels, providing a safe and reliable pressure-bearing shell for deep-sea personnel and equipment. At the same time, during the molding process of thick-walled composite materials, when the middle part of the material releases heat, the filler tin powder will absorb heat, slowing down the temperature rise of the material caused by the reaction heat. When the middle temperature reaches 161°C, the tin powder undergoes a phase transformation and produces an 11% volume expansion, compensating for the internal shrinkage stress of the product caused by the resin curing shrinkage and the crack nucleation and expansion problems it brings. After the curing is completed, the shell is cooled to room temperature to complete the transformation of the metal tin from γ-Sn to β-Sn, and further cooled to below 13°C, at which time the transformation of β-Sn to a-Sn occurs. The volume expands by 13.7% relative to the volume of γ-Sn when the curing is completed, so that the shell material matrix resin is in a state of no internal stress at the service temperature.
[0086] Step S5: taking out the internal sand core mold by physical and chemical methods to obtain a high-performance shell product.
[0087] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Although the present invention has been described in detail with reference to the above embodiments, the present invention is not limited to the above specific implementation methods. Therefore, any modification or replacement of the present invention; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the invention are included in the scope of the claims of the present invention.
Claims
1. A phase change compensation low thermal expansion coefficient resin formula, characterized in that: The formula consists of the following ingredients: 30-60 parts of liquid resin, 10-30 parts of solid resin, 5-15 parts of toughening agent, 6-35 parts of curing agent, 0.5-10 parts of accelerator, 10-80 parts of coated nano-tin alloy, and 0.1-5 parts of auxiliary agent.
2. A phase change compensation low thermal expansion coefficient resin formulation according to claim 1, characterized in that: The main resin material includes but is not limited to one or a combination of more than one of epoxy resin, polyurethane resin, polyimide resin thermoplastic or thermosetting resin; the resin formula system for dry winding of thick shell contains 10-80 parts of capsule-coated tin or tin alloy powder, with a tin content of more than 70%, a diameter of 0.05um-10um, and an addition amount of 10-80 parts by mass.
3. A phase change compensation low thermal expansion coefficient resin formulation according to claim 2, characterized in that: The high-performance phase-change heat-absorbing low thermal expansion coefficient resin formula contains 0.1-5 parts of an internal mold release agent precipitated at low temperature.
4. A phase change compensation low thermal expansion coefficient resin formulation according to claim 3, characterized in that: The formula material has a long-term stable working temperature of ≤13℃ or between 30-150℃.
5. A phase change compensation low thermal expansion coefficient resin formulation according to claim 4, characterized in that: The liquid resin is one or two of difunctional, trifunctional, and tetrafunctional thermosetting resins; the solid resin is solid bisphenol A or solid phenolic modified bisphenol A resin; the toughening agent is one or two of phenoxy resin, cyanate ester, PKHH, PEK, PEEK, PEKK, PI, carboxyl-terminated nitrile rubber, nano core-shell toughening agent, modified graphene, and carbon nanotubes; the curing agent is one or two of dicyandiamide and imidazole epoxy curing agent; and the accelerator is one or two of urea or imidazole curing agents.
6. A phase change compensation low thermal expansion coefficient resin formulation according to claim 5, characterized in that: The coated nano-tin alloy is carboxyl-terminated nitrile rubber, hydroxyl-terminated nitrile rubber, polyurea, polyurethane, polyimide coated nano-tin or tin alloy, with a particle size of 0.05-10 microns, a tin content of more than 70% in the alloy, a coating capsule layer thickness of 50nm-2um, and auxiliary agents including one or two of an internal release agent, paraffin, a coupling agent, a wetting agent, and a defoaming agent.
7. A method for preparing and using a composite prepreg tape with a phase change compensation low thermal expansion coefficient resin formula, characterized in that: The prepreg tape is prepared by hot-dip wetting and cold-demolding continuous pultrusion. Due to the stability of the a-Sn crystal structure, the long-term application environment temperature of the material system is above 30°C or below 13°C, and the short-term use temperature is at a high temperature far from the melting point of tin.
8. The method for preparing and using a composite prepreg tape with a phase change compensation low thermal expansion coefficient resin formula according to claim 7, characterized in that: Resin system preparation steps: Step S1: slightly oxidizing the surface of tin powder in the air, treating the surface with a coupling agent, and preparing capsule-coated tin powder by a sol-gel method; taking liquid resin, adding the capsule-coated tin powder into the liquid resin, stirring, and performing three-roll grinding to evenly disperse the powder to form a tin powder pre-dispersed paste for standby use; Step S2: taking liquid resin, adding toughening agent into the liquid resin, heating and stirring at high speed to make it dissolve evenly in the resin to form toughening masterbatch for later use; Step S3: taking liquid resin, adding curing agent into the liquid resin, stirring, and three-roll grinding to make it evenly dispersed to form a curing agent pre-dispersed paste for standby use; Step S4: taking liquid resin, adding accelerator to the liquid resin, stirring, and three-roll grinding to make it evenly dispersed to form an accelerator pre-dispersed paste for standby use; Step S5: Add toughening masterbatch, liquid resin and solid resin to the dispersion axe in proportion, heat and stir, and vacuum to remove bubbles while stirring; after the materials are evenly mixed, cool to 70-80°C, add additives, curing agent pre-dispersed paste, tin powder dispersion paste and accelerator pre-dispersed paste in sequence, stir and mix evenly, discharge the materials, bag them, cool to room temperature in a ventilated place for use.
9. The method for preparing and using a composite prepreg tape with a phase change compensation low thermal expansion coefficient resin formula according to claim 8, characterized in that: Preparation steps of dry prepreg tape system: Step S1: Design a hot soaking cooling drawing method carbon fiber prepreg tape mold, the mold is equipped with a resin supply system with vacuum degassing and heating functions, a heating module, a cooling and heating temperature control module, a cooling end and a vacuum degassing module, a rounded corner structure at both ends of the mold, a slight taper from the inlet to the outlet of the cavity, and a chrome-plated inner wall and mirror polished; Step S2: The carbon fiber is led out from the tension release frame, and after being spread by the yarn spreading device, it enters the mold under the action of the rear-stage traction and winding device and continuously moves forward at a set speed. The resin enters the mold cavity under the action of the glue injection machine and the fiber traction and dragging belt; the resin continues to heat up and melt inside the mold to fully infiltrate the fiber, and then gradually cools down and evacuates during the cooling process. The resin itself with viscosity acts as a gas sealant at both ends of the mold cavity. Under the combined action of temperature, mold extrusion and vacuum, the degassing and compaction process of the resin material is completed; Step S3: under the action of the traction tension at the die mouth, the material continues to move forward into the low-temperature solidification stage. As the temperature decreases, the viscosity of the resin attached to the fibers increases sharply and gradually has the load-bearing capacity to bond the fibers into a whole. In this process, the temperature decrease causes the material to cool and shrink and fall off from the inner wall of the mold. The release agent originally dissolved in the resin system is reduced in solubility due to the temperature decrease and precipitates to the surface of the material to lubricate and reduce the resistance of the solid material to further escape from the mold cavity. The low-temperature solid resin attached to the fiber surface escapes from the mold cavity with the fiber under the traction of the fiber and enters the low-temperature closed traction chamber. Step S4: The low-temperature prepreg tape enters a low-temperature sealed traction chamber. The low temperature ensures that the resin is hard and can bear the load. At the same time, the sealed chamber can prevent external moisture from entering and generating condensed water. The traction device in the traction chamber gives the low-temperature prepreg tape a continuous forward traction force, driving the fiber into the mold, cooling the prepreg tape material and removing it from the mold cavity, thereby realizing the continuous production of the prepreg tape. Step S5: After the prepreg tape comes out of the low-temperature traction chamber, it is softened by hot air heating, coated with a hot roller, and rolled up to form a prepreg tape material for dry winding; Step S6: The rolled prepreg tape material after coating and rolling is sealed, dried, and stored away from light at room temperature of 25° C. to 30° C. for later use.
10. The method for preparing and using a composite prepreg tape with a phase change compensation low thermal expansion coefficient resin formula according to claim 9, characterized in that: Steps for preparing the shell using dry prepreg tape material: Step S1: using molding sand and low melting point metal to process and prepare a winding core mold according to the shell design size, and coating the vacuum air bag and air guide felt vacuum forming material; Step S2: The prepared prepreg tape within the validity period is wound layer by layer on a core mold with a vacuum system under tension using a winding device according to the design parameters, and the wound preform is removed and placed in a designed circular mold shell coated with a release agent, and the mold gap is sealed with a sealant and then locked with screws; Step S3: Wrap the outer layer of the mold and the inner wall of the shell with a composite material-molded belt-shaped vacuum film, seal with a sealing strip, connect the vacuum device and put the whole into an autoclave; Step S4: After continuous vacuuming, the autoclave is slowly heated according to the set program in the vacuumed state, and the vacuuming is continued and the shell is cured according to the set process; as the temperature in the autoclave gradually increases, the composite shell resin gradually softens and flows, and the flowing resin under the vacuum fills the small gaps generated in the process, and the small amount of bubbles entrained in the resin also gradually grows and breaks and is discharged under the vacuum; compressed air is introduced into the autoclave, and the sum of the air pressures of the external compressed air and the vacuum degree is called the total air pressure because the mold shell and the inner wall of the product are simultaneously subjected to the total air pressure of the external compressed air and the vacuum degree. The total air pressure on the outer wall acts on the circular mold shell, and the total air pressure on the inner wall acts on the winding shell, so that the bubbles in the shell resin are further squeezed and broken and discharged, and the entire shell is subjected to the total air pressure of the radial outward expansion, so that the shell is close to the inner wall of the molding mold to obtain a circular product shape, and the shell is While expanding outward, the axially wound fibers are tensioned to minimize the microscopic buckling of the fibers inside the product during the process. During the molding of thick-walled composite materials, when the middle part of the material releases heat, the filler tin powder will absorb heat and reduce the temperature rise. When the temperature rises to the tin phase change temperature of 161°C, the tin powder undergoes a phase change and produces an 11% volume expansion, which compensates for the molding stress caused by excessive heat release and curing shrinkage of the resin. After the curing is completed, the shell is gradually cooled to room temperature to complete the transformation of γ-Sn to β-Sn and further cooled to below 13°C. At this time, a slow transformation of β-Sn to a-Sn occurs, and the volume expands by 13.7% relative to the volume of γ-Sn when the curing is completed, reducing or eliminating the shrinkage internal stress inside the cured resin material, and reducing the germination and expansion of resin cracks caused by the release of internal stress during repeated loading during the service of the material. Step S5: The internal sand core mold is removed by physical and chemical methods to obtain a high-performance shell product.
Citation Information
Patent Citations
Phase-changed heat insulation polyolefin foam material and preparation method thereof
CN103102552A
One-step molding method for fiber-reinforced resin composite under vacuum impregnation
CN103434144A
Low thermal expansion coefficient cyanate ester resin composite and preparation method thereof
CN105482453A
Preparation method and application of thermoplastic resin toughening particles
CN114806176A
Adhesive, method for manufacturing the same, and heat insulating mold
JP2014181294A
Cited By
Shockproof dry-type transformer
CN121237533A
Shockproof dry-type transformer
CN121237533B